AB0606 Lupus Myocarditis in the Western Cape, South Africa: Analysis of Clinical and Echocardiographic Features. (9th June 2015) - Du Toit, R.; Herbst, P.; van Rensburg, A.; du Plessis, L.; Reuter, H.; Doubell, A.
Abstract : Background: Lupus myocarditis (LM) is a serious manifestation of systemic lupus erythematosus (SLE). LM in patients of African American ethnicity has an increased prevalence and higher mortality compared to other ethnic groups. In the mixed racial population of the Western Cape, South Africa, no data exists on the clinical features and outcome of LM. Echocardiography is frequently used to support the diagnosis of LM. Speckle tracking (ST) is more sensitive than standard imaging in the detection of left ventricular (LV) dysfunction. Literature on the use of ST in patients with clinically evident LM is limited. Objectives: To give a comprehensive description of the clinical and echocardiographic features of acute LM in a mixed racial population. Methods: Clinical records (over 6 years) of adult SLE patients at a tertiary referral centre were retrospectively screened for a clinical and echocardiographic diagnosis of LM. Clinical features, laboratory results, management and outcome were described. Echocardiographic images stored in a digital archive were reanalysed (where views allowed), including LV regional wall motion abnormalities (RWMA) and longitudinal strain through ST. Results: 28 patients (6.1%) met inclusion criteria: 92.9% were female and 89% were of mixed racial origin. 54% of patients presented with LM within 3 months after being diagnosed with SLE. Median SLE disease activity index was 17.5 (IQR:12.3-24) and 50% of patients had concomitant lupus nephritis. Laboratory results included: low complement (92.3%); urinary protein >0.5g/day (83%); increased aRNP (62%). Initial (at time of diagnosis) and most recent echocardiographic data are summarised in table 1 . Treatment included corticosteroids (96%) and cyclophosphamide (75%); 14% of patients required additional immunosuppression. Clinical improvement occurred in 67% of patients (563 days, median); 2 patients relapsed. Though the median LV ejection fraction (LVEF) improved from 35 to 47%, reduced longitudinal strain and RWMA persisted in most patients (Table 1 ). Overall mortality was high (12/28): 5/28 (17.9%) died due to LM compared to 2/24 (8.3%) in another case series. Mortality due to LM and/or treatment related complications were 35.7% (10/28). Conclusions: This is the largest reported case series on LM. The mixed racial population had a similar prevalence, but higher mortality compared to other ethnic groups (published literature). An increased awareness towards an early diagnosis is essential, especially in recently diagnosed SLE patients with concomitant lupus nephritis. ST (not previously described in acute LM) and RWMA showed persistent LV dysfunction despite an improved LVEF and could be utilised as a sensitive diagnostic tool in LM. Disclosure of Interest: None declared